Mesh Infection in Sacrocolpopexy: A Novel Approach to Management - Reeti Mehra; Shubhi Bandlish (Wolters Kluwer Medknow Publications, 2024)
Surgical mesh has been in use for urogynecological surgeries for a long, but they come with their own side effect profile and maybe life-altering consequences. We discuss a novel method of management of mesh erosion and infection in a patient with mesh sacrocolpopexy.